Understanding Cough Ethics and Changes of Behavior of Kindergarten Teachers in the Work Area of Puskesmas Sedayu I: Community-Based Health Efforts - Sistia Utami; Mora Claramita; Wahyudi Istiono (Faculty of Medicine, Public Health, and Nursing, 2020)
Background: Cough cases are increasing every year. The most common cause is a virus. Coughing is influenced by endurance, Cough Ethics, and Handwashing with Soap/Cuci Tangan Pakai Sabun (CTPS). Transmission occurs through droplets in the air from the patient when coughing or sneezing. We need to educate the community to minimize transmission, especially among children. Ultimately, this speeds up the healing process. Objective: This study aimed to provide an understanding of Cough Ethics and behavior change using narrative in action to kindergarten teachers. Method: This study used descriptive-analytic qualitative methods with narrative in action. The subjects of the study were a population of kindergarten teachers in the working area of the Puskesmas Sedayu 1, selected purposive snowball sampling. Retrieval of data was done through the observation stage, pre-narrative in action activities, the narrative in action, post narrative in action activities, and the final observation stage in kindergarten. Result: Observations were done at the school to find out the infrastructure. Observation before and after the demonstration showed there were improvements and concluded that all can demonstrate the Cough Ethics and CTPS. Watching the Cough Ethics video, CTPS, followed by the dialogue, motivation, education, persuasion, promotion were empowering for the teachers to change their behavior. All groups when coughing or sneezing covered their nose and mouth with a tissue, mask, or the inner side of elbow arm or expelled phlegm on the ground, lodong/special place like a jar, and toilet. Conclusion: Narrative in action activities are an alternative way of providing understanding to change behavior. Watching videos makes it easy to explain the Ethics of Cough. Practice is needed to improve the skills of narrative in action.